Dampak Budaya Korean Pop Dalam Perilaku Konsumerisme di Kalangan Penggemar K-Pop UKM Hallyu-Up Edutainment - Ilsya Mulya Insani, Ilsya Mulya Insani; Iqbal, Muhamad; Arief Rakhman, Muhammad (The Indonesian Journal of Social Studies, 2024)
In the current era of globalization, cultural development is increasingly rapid, and cultural change is shown by a new culture in society, such as the phenomenon of popular culture, namely culture. Korean Pop which is increasingly loved and very popular with the wider community, especially Indonesian teenagers including students in the UKM Hallyu-Up Edutainment community. This research aims to analyze the extent of the impact of Korean Pop culture towards consumerist behavior carried out by fans of K-Pop which is seen from behavioral indicators of prestige, social status, lifestyle expression, luxury and honor. This research data uses a qualitative approach with a case study method where data collection is carried out using in-depth interviews, observation and documentation. The research results show that culture K-Pop has an impact on student consumerism behavior in prestige behavior through purchasing music albums or merchandise K- Pop namely because it fulfills a wish or desire. Purchase of cultural products Korean Pop makes a reference in students' social status to show their identity as fans of K-Pop. Culture Korean Pop has the impact of financial waste on students in expressing their lifestyle of consuming various products K-Pop. Culture Korean Pop provide a self-indulgent impact on students in the luxury of consuming products K-Pop of the product brand branded or famous, and culture K-Pop has the impact of imitating behavior, self-esteem, showing off or prestige towards students in the honor of consuming the product K-Pop so that his existence as a fan continues to be recognized.